Public employment programmes in the care economy: The case of South Africa - Lerato Shai (International Labour Organization (ILO), 2021)
The COVID-19 pandemic and associated economic crisis have increased unemployment levels in the care economy, detrimental effects of which are felt by care workers, the majority of whom are women. The South African experience shows that Public Employment Programmes (PEPs) have contributed to the progressive realisation of decent work where as a first step in the trajectory, they have recognised and renumerated care related labour as work. This case study raises a series of questions for further consideration about the role of PEPs in this context, particularly their efficacy in the provision of direct care services. @The COVID-19 pandemic and associated economic crisis have increased unemployment levels in the care economyith detrimental effects for care workers, the majority of whom are women . Additionally, the current context is highlighting inherent weaknesses in healthcare systems, exacerbating gender imbalances in the provision of paid and unpaid care work, and offering a micro experience of the consequences of failure to respond to the increasing demand for care globally. Given their focus on labour intensity and greater levels of employment per unit of government expenditure, PEPs are a crucial instrument to respond to these challenges. This paper draws on learnings from South Africa to outline how PEPs can contribute to the reduction of employment, service provision and transitions to decent work in the care economy. Moreover, it provides insights into of how PEPs can form part of a support package to respond to the economic and social effects of COVID-19. The South African experience shows that PEPs have contributed to the progressive realisation of decent work where as a first step in the trajectory, they have recognised and renumerated care related labour as work. However, where unemployment is persistent, the market fails to produce sustainable work opportunities at the levels required, and fiscal constraints reduce the state's is ability to absorb PEPs workers, the programmes tend to lead to slow or non-existent progression beyond this first step. Furthermore, while the paper shows that the South African government's Presidential Employment Stimulus provided much needed relief to the effects of COVID-19, it also highlighted the limitations of PEPs as a response to sector specific challenges within the care economy. The case study raises a series of questions for further consideration about the role of PEPs in such contexts, particularly their efficacy in the provision of direct care services. Several options are available to government, including a recognition of such services as long-term and ongoing. Regardless of the policy choices made to respond to the different challenges, the state needs to embark on a fundamental redesign in the funding framework for all PEPs in the care economy to improve wage levels and structurally change how workers are transitioned into more decent forms of work.
Keywords: 330; labour intensive employment; care economy; COVID-19